Oil Price Shocks and Macroeconomic Instability in Nigeria: Evidence from GVAR - Jibril, Nawasi Uba; Halaç, Umut (International Journal of Contemporary Economics and Administrative Sciences, 2019)
The study examines the relationship between oil price shocks and selected macroeconomic variables in Nigeria. It adopts a Global Vector Autoregressive (GVAR) model, which includes Nigeria’s major trade partners, in examining the relationship. This provides a holistic picture of how oil price shocks are conveyed to Nigeria via the first round as well as through the spillover effects. The variables employed are Real Gross Domestic Product (y), inflation (Dp), short-term interest rate (r), money supply (ms), and real effective exchange (epeps) as the domestic variables, while oil price is included as global variable. Quarterly data were used spanning the period 1979Q2 to 2013Q1. The economies included are Nigeria, the United States, Euro Area, India, China, Brazil, United Kingdom and South Africa. The findings of the study reveal that an upsurge in oil price leads to increase in real output, money supply as well as a mild increase in the real effective exchange rates of Nigeria while inflation and short-term interest rate fall.